Palladium‐Catalyzed Silacyclization of (Hetero)Arenes with a Tetrasilane Reagent through Twofold C−H Activation. Issue 13 (24th February 2021) - Wang, Dingyi; Li, Mingjie; Chen, Xiangyang; Wang, Minyan; Liang, Yong; Zhao, Yue; Houk, Kendall N.; Shi, Zhuangzhi
Abstract: The use of an operationally convenient and stable silicon reagent (octamethyl‐1, 4‐dioxacyclohexasilane, ODCS) for the selective silacyclization of (hetero)arenes via twofold C−H activation is reported. This method is compatible with N‐containing heteroarenes such as indoles and carbazoles of varying complexity. The ODCS reagent can also be utilized for silacyclization of other types of substrates, including tertiary phosphines and aryl halides. A series of mechanistic experiments and density functional theory (DFT) calculations were used to investigate the preferred pathway for this twofold C−H activation process. Abstract : A method is reported for the selective silacyclization of (hetero)arenes via twofold C−H activation. An operationally convenient and stable silicon reagent, octamethyl‐1, 4‐dioxacyclohexasilane (ODCS), is employed.